College Students’ Cognitive and Affective Attitude toward Higher Education and Their Academic Engagement - Abun, Damianus; Magallanes, Theogenia; Incarnacion, Mary Joy (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The study was intended to determine the college students’ cognitive and affective attitude toward higher education and how it affects their academic engagement. In order to proceed with the study, theories on human attitude and human behaviour and academic engagement were discussed. Related literatures were reviewed to strengthen the theory of the study and the validated questionnaires were used to gather the data. The study used descriptive correlational research design and supplied by inquiries. To interpret the data, the statistical tools were used such as Mean and Pearson r. Mean was used to measure the cognitive and affective attitude of students toward education and their academic engagement. Pearson r was used to determine the relationship between cognitive and affective attitude of students toward higher education and academic engagement. The study found that students’ cognitive and affective attitude toward higher education correlates significantly to the academic engagement.